2021
DOI: 10.3390/ma14205930
|View full text |Cite
|
Sign up to set email alerts
|

Damage Fracture Characterization of Asphalt Mixtures Considering Freeze–Thaw Cycling and Aging Effects Based on Acoustic Emission Monitoring

Abstract: Freeze–thaw (F–T) cycling and aging effects are the main factors contributing to the deterioration of asphalt mixtures. The acoustic emission (AE) technique enables real-time detection regarding the evolution of internal damage in asphalt mixtures during the loading process. This study set out to investigate the effects of F–T cycling and aging on the damage characteristics of asphalt mixture under splitting loads. Firstly, the Marshall specimens were prepared and then exposed to various numbers of F–T cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…At the same time, wheel rolling and dynamic water scouring will aggravate the damage of salt storage asphalt pavement. In the salt storage asphalt mixture, deliquescence will occur at the filler, which greatly increases the number and porosity of the mixture and increases the contact area with water [75]. High-speed, high-pressure, hydrodynamic scouring and freeze-thaw will increase the size and number of pores, accelerate the salt dissolution, and thus aggravate the freeze-thaw damage [76,77].…”
Section: Water Stability Performancementioning
confidence: 99%
“…At the same time, wheel rolling and dynamic water scouring will aggravate the damage of salt storage asphalt pavement. In the salt storage asphalt mixture, deliquescence will occur at the filler, which greatly increases the number and porosity of the mixture and increases the contact area with water [75]. High-speed, high-pressure, hydrodynamic scouring and freeze-thaw will increase the size and number of pores, accelerate the salt dissolution, and thus aggravate the freeze-thaw damage [76,77].…”
Section: Water Stability Performancementioning
confidence: 99%
“…Fan Z et al [27] observed that the fatigue life of asphalt mixtures reduced with saturation and freezingthawing cycles increasing. Fu L. et al [28] showed that freezing and thawing cycles changed the failure type of asphalt mixtures, made it harder for microcracks to form early on, sped up the growth of macrocracks, and made it easier for asphalt and aggregates to separate. Wang T. et al [29] found the tensile modulus of steel slag, basalt, and recycled aggregate permeable asphalt concrete decreased by 80-90% after 20 freezing-thawing cycles.…”
Section: Introductionmentioning
confidence: 99%